Avaliação da pressão arterial sistêmica em cães obesos: Comparação entre os métodos oscilométrico e doppler ultrassônico - Pereira-Neto, Gláucia B.; Brunetto, Márcio A.; Champion, Tatiana; Ortiz, Edna M.G. [UNESP]; Carciofi, Aulus C. [UNESP]; Camacho, Aparecido A. [UNESP] (FapUNIFESP (SciELO), 2014)
Obesity is the most common nutritional problem in dogs and it can cause various harmful effects on animal health. However, the effect of this condition on systolic blood pressure (SBP) in obese dogs is controversial. The indirect method of measuring PAS is the most commonly used in veterinary medicine for the diagnosis of systemic hypertension, because it is more practical and easy to access. There is little scientific information about the comparison of the two non-invasive methods of measurement of blood pressure in obese dogs. Therefore, the objective of this study was to evaluate the SBP in obese dogs by comparing both indirect methods of measuring blood pressure, with oscillometric and doppler vascular in order to verify the differences in blood pressure values, but also the best method to assess the SBP dogs in this body score condition. The study complain blood pressure measurement of 50 dogs, with were divided in obese dogs with mean body condition score (BCS) of 8.42±0.50 (n=25) and dogs with ideal BCS of 4.56±0.51 (n=25). At comparison of blood pressure values, SBP values obtained by doppler method (152±16mmHg) were higher than the oscillometric (136±11mmHg). Correspondence analysis determined by multivariate statistical analysis showed correlation between body condition and the procedure of the SBP. These findings suggest that the indirect method doppler can better reflect the SBP in obese dogs.
Systemic blood pressure evaluation by oscillometric versus doppler ultrasonographic methods in obese dogs
Keywords: Canine; Hypertension; Indirect method; Obesity